Trans Fatty Acid in Selected Malaysian Foods and its Association with Intake Pattern and Contents in Human Milk of Lactating Mothers in Bandar Baru Bangi, Malaysia - Daud, Akmar Zuraini (2012)
Many countries have enforced regulation on TFA content in food labelling except for Malaysia. The unknown amount of TFA in local food have been hypothesized to impact the health, as well as disruption on nutritional value of human milk. The presence of TFA in human milk have been implicated in significant “displacement” of essential fatty acid, making the milk less energy dense. Therefore, the objectives of this study were to determine the TFA intake of Malaysian lactating mothers in association with human milk composition. The study consists of two parts; Part 1: Analysis of TFA content in selected food; bakery products, snacks, milk and dairy products, cooking oils and semisolid fats, fast food, breakfast cereals, roti canai, chapatti, thosai, drinking cereals, sweetened milk and ice cream and Part 2: Determination of pattern of intake for selected Malaysian food and TFA content in human milk among lactating mothers. The results from Part 1 showed that the highest amount of TFA was found in fast food which was <0.001g - 8.49g/100g lipid or <0.001g - 1.97g/100g food whereas, the lowest amount was found in snack, which was <0.001g - 1.89g/100g lipid or <0.001g - 0.57g/100g food. Besides that, TFA level in most of food tested is still reasonably low. In terms of TFA isomers, major isomers found in studied samples were linoelaidic acid (18:2t9,12) (41.19%) and elaidic acid (18:1t9) (35.87%),whereas, other isomers were lower than 20%. In Part 2 of this study, there were 101 lactating mothers recruited from Klinik Kesihatan Bandar Baru Bangi. Information on sociodemographic, reproductive data, anthropometric, Food Frequency Questionnaires (FFQ) score for 7 food groups and dietary consumption parameters were collected for this part. The TFA content in human milk was 2.94±0.96% fatty acid which is considered low as the detected value is less than 4% fatty acid. The most abundantly found TFA isomer in human milk is linoelaidic acid (18:2t9,12) (1.44±0.60% fatty acid) whereas vaccenic acid (18:1t11) (0.15±0.12% fatty acid) was found to be the least. From sub experiment result, the daily intake of TFA 18 lactating mothers is 1.27±0.26g/100glipid/day/person which is below as compared with countries like US and Denmark. The relationships between frequencies food consumption and TFA level in human milk were assessed using non-parametric Spearman Rho test (SPSS version 15). The results showed only 10 of the food items; bun, chicken burger, shortening, powdered milk, cheese burger, sweetened milk, blended oil, mayonnaise, corn oil and ice cream were identified to give an effects towards total TFA and TFA isomers in human milk. None of the dietary parameters observed give any effect on total TFA in human milk. In regards to lipid composition of human milk, the finding showed that, total TFA in human milk could decrease Arachidonic acid AA (20:4) content but have no effect on total fat, linoleic acid (18:2), Eicosapentanoic acid (EPA) (20:5) and Docosahexaenoic acid (DHA) (22:6) content. It was demonstrated that, lipid composition of human milk was not significantly affected by current TFA intake. It was probably due to low consumption of TFA among lactating mothers. The extensively usage of palm oil by Malaysian population may also contribute to low consumption of TFA.